(untitled) (The Arab Journal of Administration, 2026)
The advancement and civilization of a culture are reflected in the empowerment of women. It is essential and necessary for the overall growth of civilization to succeed. This study tries to provide a response to the topic, Do Women Still Face Workplace Challenges After Empowerment? In the context of examining the contribution made by the “Kingdom’s vision 2030” to Saudi women’s empowerment. The objective of this study is to shed light on the role of Saudi women working in community development, to identify the most significant challenges and issues facing Saudi women generally and those working in the public educational sector, and to offer solutions. The researcher used qualitative research techniques and a descriptive-analytical strategy (semi-structured interviews). Thirteen Saudi women who are working in public education administration in Jeddah and Riyadh cities were subjected to interviews. The study’s factors were divided into three categories: organizational challenges, societal challenges, and family challenges. The study concluded that the Saudi leadership has increasingly acknowledged the value of Saudi women. The administration made improving the position of women in several growth sectors, especially economic growth, a top priority. Saudi society continues to disapprove of Saudi women’s employment and participation in the labour force. The Saudi family is crucial in supporting working Saudi women and assisting them in excelling in their careers and professions. The researcher suggested that Saudi society’s perception of working Saudi women must be changed. Moreover, it is important to implement numerous radical changes in hiring practices and to attain gender parity in job chances.